THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN FOREIGN LANGUAGE TEACHING - Nabidullin S. Aibolat; Nurimbetova Balkenzhe (Interdisciplinary Science Studies, 2025)
This article explores the pedagogical, technological, and methodological impact of Artificial Intelligence (AI) in contemporary foreign language teaching, offering an expanded and more detailed overview of how AI-driven solutions support the transformation of modern educational practices. It discusses various innovative digital tools that enable personalized learning, automated assessment, adaptive instruction, autonomous language practice, and enhanced accessibility for learners with diverse needs. The study provides an in-depth description of intelligent tutoring systems, speech recognition technologies, AI-based feedback generators, and adaptive learning platforms as essential components of digital language pedagogy. Furthermore, it highlights AI’s contribution to learner motivation, inclusive education, and access to authentic linguistic input, demonstrating that when applied responsibly and ethically, AI significantly enhances teaching efficiency and supports the development of independent, confident, and digitally competent foreign language learners